My qustion is for the following
the problem reads as follows
(x-1)^2 = 7
x-1=+- sqrt 7
x= 1+- sqrt 7
the method they use was factoring in order to simplify the equation to make it easier is this correc?
x^2-9x-4=6
x^2-9x-10=0
(x-10)(x+1)=0
What method did they use here I think its simplifying but i am not sure?
4x^2-8x+3=5
4x^2-8x-2=0
2(2x^2-4x-1)=0
2x^2-4x-1=0
here the method that they use was first factoring then simplefiying and then they will use the quadratic formula is this correct?
You are right on all counts.